Tissue expression of retinoic acid receptor alpha and CRABP2 in metastatic nephroblastomas - Ana Paula Percicote; Gabriel Lazaretti Mardegan; Elizabeth Schneider Gugelmim; Sergio Ossamu Ioshii; Ana Paula Kuczynski; Seigo Nagashima; Lúcia de Noronha (BMC, 2018)
Abstract Background Nephroblastoma or Wilms tumor is the most frequent kidney cancer in children and accounts for 98% of kidney tumors in this age group. Despite favorable prognosis, a subgroup of these patients progresses to recurrence and death. The retinoic acid (RA) pathway plays a role in the chemoprevention and treatment of tumors due to its effects on cell differentiation and its antiproliferative, anti-oxidant, and pro-apoptotic activities. Reports describe abnormal cellular retinoic acid-binding protein 2 (CRABP2) expression in neoplasms and its correlation with prognostic factors and clinical and pathological characteristics. The aim of this study was to evaluate the immunohistochemical expression of retinoic acid receptor alpha (RARA) and CRABP2 in paraffin-embedded samples of nephroblastomas via semiquantitative and quantitative analyses and to correlate this expression with prognostic factors. Methods Seventy-seven cases of nephroblastomas were selected from pediatric oncology services. The respective medical records and surgical specimens were reviewed. Three representative tumor samples and one non-tumor renal tissue sample were selected for the preparation of tissue microarrays (TMA). The Allred scoring system was used for semiquantitative immunohistochemical analyses, whereas a morphometric analysis of the stained area was employed for quantitative evaluation. The nonparametric Mann-Whitney test was used for comparisons between two groups, while the nonparametric Kruskal-Wallis test was used to compare three or more groups. Results Immunopositivity for RARA and CRABP2 was observed in both the nucleus and cytoplasm. All histological components of the nephroblastoma (blastema, epithelium, and stroma) were positive for both markers. RARA, based on semiquantitative analyses, and CRABP2, bases on quantitative analyses, exhibited increased immunohistochemical expression in patients with metastasis, with p values of 0.0247 and 0.0128, respectively. These findings were similar to the results of the quantitative analysis of RARA expression, showing greater immunopositivity in tumor samples of patients subjected to pre-surgical chemotherapy. No significant correlation was found with the other variables studied, such as disease stage, anaplasia, risk group, histological type, nodal involvement, and clinical evolution. Conclusions Semiquantitative and quantitative analyses of the markers RARA and CRABP2 indicate their potential as biomarkers for tumor progression and their participation in nephroblastoma tumorigenesis.